Heme-Derived Metabolic Signals Dictate Immune Responses - Canesin, Giacomo; Hejazi, Seyed M.; Swanson, Kenneth D.; Wegiel, Barbara (Frontiers in Immunology, 2020)
Heme is one of the most abundant molecules in the body acting as the functional core of hemoglobin/myoglobin involved in the O2/CO2 carrying in the blood and tissues, redox enzymes and cytochromes in mitochondria. However, free heme is toxic and therefore its removal is a significant priority for the host. Heme is a well-established danger-associated molecular pattern (DAMP), which binds to toll-like receptor 4 (TLR4) to induce immune responses. Heme-derived metabolites including the bile pigments, biliverdin (BV) and bilirubin (BR), were first identified as toxic drivers of neonatal jaundice in 1800 but have only recently been appreciated as endogenous drivers of multiple signaling pathways involved in protection from oxidative stress and regulators of immune responses. The tissue concentration of heme, BV and BR is tightly controlled. Heme oxygenase-1 (HO-1, encoded by HMOX-1) produces BV by heme degradation, while biliverdin reductase-A (BLVR-A) generates BR by the subsequent conversion of BV. BLVR-A is a fascinating protein that possesses a classical protein kinase domain, which is activated in response to BV binding to its enzymatic site and initiates the downstream mitogen-activated protein kinases (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. This links BLVR-A activity to cell growth and survival pathways. BLVR-A also contains a bZip DNA binding domain and a nuclear export sequence (NES) and acts as a transcription factor to regulate the expression of immune modulatory genes. Here we will discuss the role of heme-related immune response and the potential for targeting the heme system for therapies directed towards hepatitis and cancer.